Sifat fisik, mekanik dan akustik papan partikel berbahan dasar batang jagung (Zea mays L.) [Physical, mechanical and acoustical characteristics of particleboard made from corn stalk (Zea mays L.)] - Lilik Astari; Firda Aulya Syamani; Kurnia Wiji Prasetiyo (Jurnal Riset Industri Hasil Hutan, 2019)
Corn stalk is considered as agricultural by-products that is abundance and easy to obtain in Indonesia. Corn stalk is an agricultural by-product that highly potential to be exploited as raw material for particleboard production. The research was aimed to evaluate the use of corn stalk in the production of particleboard especially for its acoustics and physical properties. Targeted board density was 0.5 g/cm3and 0.7 g/cm3. The Adhesive used in the board production were urea formaldehyde 10%, phenol formaldehyde 10% and isocyanate (pMDI) 10% based on their solid content. Board dimension was 35 x 35 x 1 cm. The pressure used was 25 kgf/cm2, temperature of 130℃ and 150℃ for 10 minutes. After production, boards were conditioned at room temperature for 7 days prior to testing. The standard for physical and mechanical properties JIS A 5908-2003, Acoustic properties testing was according to JIS A 1405-1963. The result shows that particleboard with isocyanate adhesive both with low and medium density had the best result. Acoustic testing shows that the highest sound absorption coefficient was given by particleboard with isocyanate at frequency 1500 Hz.